Overview of~EU and Global Conditions for~the~Transformation of~the TCLF Industry on~the Way to~a~Circular and Digital Economy (Case Studies from Poland) - Radosław Dziuba; Małgorzata Jabłońska; Katarzyna Ławińska; Zofia Wysokińska (Comparative Economic Research. Central and Eastern Europe, 2022)
The article aims to review the changes that have taken place in the European and global TCLF (Textiles-Clothing-Leather-Footwear) sector over the last decade from the perspective of new requirements of pursuing a circular and, especially in recent years, a digital economy. The paper describes the changes in the components of this industry (formerly called the light industry) in the European Union and the world economy in the context of sustainable development requirements and the effects of climate change. Recent European and global programs mainly aim to achieve the circular economy's strict requirements, including reducing pressure on natural resources, to achieve climate neutrality by the end of 2050. This positive change for our planet is also supported by the pursuit of the development of the digital economy.
Keywords: O13; 330; textiles; clothing; leather; footwear; transformation; circular economy; digital economy; European Union; world economy; Poland